Spontaneous phenotypic suppression of GacA-defective Vibrio fischeri is achieved via mutation of csrA and ihfA - Foxall, Randi L. (BMC Microbiol, 2015)
BACKGROUND: Symbiosis defective GacA-mutant derivatives of Vibrio fischeri are growth impaired thereby creating a selective advantage for growth-enhanced spontaneous suppressors. Suppressors were isolated and characterized for effects of the mutations on gacA-mutant defects of growth, siderophore activity and luminescence. The mutations were identified by targeted and whole genome sequencing. RESULTS: Most mutations that restored multiple phenotypes were non-null mutations that mapped to conserved domains in or altered expression of CsrA, a post-transcriptional regulator that mediates GacA effects in a number of bacterial species. These represent an array of unique mutations compared to those that have been described previously. Different substitutions at the same amino acid residue were identified allowing comparisons of effects such as at the R6 residue, which conferred relative differences in luminescence and siderophore levels. The screen revealed residues not previously identified as critical for function including a single native alanine. Most csrA mutations enhanced luminescence more than siderophore activity, which was especially evident for mutations predicted to reduce the amount of CsrA. Although CsrA mutations compensate for many known GacA mutant defects, not all CsrA suppressors restore symbiotic colonization. Phenotypes of a suppressor allele of ihfA that encodes one subunit of the integration host factor (IHF) heteroduplex indicated the protein represses siderophore and activates luminescence in a GacA-independent manner. CONCLUSIONS: In addition to its established role in regulation of central metabolism, the CsrA regulator represses luminescence and siderophore as an intermediate of the GacA regulatory hierachy. Siderophore regulation was less sensitive to stoichiometry of CsrA consistent with higher affinity for the targets of this trait. The lack of CsrA null-mutant recovery implied these mutations do not enhance fitness of gacA mutants and alluded to this gene being conditionally essential. This study also suggests a role for IHF in the GacA-CsrB-CsrA regulatory cascade by potentially assisting with the binding of repressors of siderohphore and activators of luminescence. As many phosphorelay proteins reduce fitness when mutated, the documented instability used in this screen also highlights a potentially universal and underappreciated problem that, if not identified and strategically avoided, could introduce confounding variability during experimental study of these regulatory pathways. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-015-0509-2) contains supplementary material, which is available to authorized users.